2006
DOI: 10.1097/01.opx.0000204510.08026.7f
|View full text |Cite
|
Sign up to set email alerts
|

Visual Function in Patients With Choroidal Neovascularization Resulting From Age-Related Macular Degeneration: The Importance of Looking Beyond Visual Acuity

Abstract: Understanding the impact of vision loss on patients with CNV resulting from AMD and assessing treatment benefits requires assessment of overall quality of vision. Primary care physicians and optometrists have an important role in ensuring that patients receive the best possible care, which can be aided by prompt referral to an ophthalmologist or retina specialist and collaboration with low-vision specialists and optometrists who together can make detailed assessments of overall quality of vision, implement app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 71 publications
1
61
1
2
Order By: Relevance
“…As florestas são espaços vitais que podem permanecer inalterados por longo tempo. te em estudos com novas terapias para doenças que acometem o campo visual central (10) . Para realizá-la, é necessário um conjunto de textos homogêneos quanto ao conteúdo e forma, e que sejam lidos com velocidades comparáveis, para que o pesquisador possa oferecer diferentes textos em diferentes consultas, ou realizar múltiplas medidas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…As florestas são espaços vitais que podem permanecer inalterados por longo tempo. te em estudos com novas terapias para doenças que acometem o campo visual central (10) . Para realizá-la, é necessário um conjunto de textos homogêneos quanto ao conteúdo e forma, e que sejam lidos com velocidades comparáveis, para que o pesquisador possa oferecer diferentes textos em diferentes consultas, ou realizar múltiplas medidas.…”
Section: Discussionunclassified
“…Além disso, habilidade de leitura tem sido incluída como padrão de medida da visão, e tem se mostrado mais sensível do que a medida da acuidade visual na detecção desses problemas (10)(11)(12) .…”
Section: Resumo Introduçãounclassified
“…The effect, however, of a six letter loss of CS has been reported to have a similar impact on self-reported visual disability as a 15 letter loss of VA (Rubin et al, 2001). The inclusion of CS in visual assessment of macular disease patient may be useful in monitoring disease progression, evaluating the benefit of treatment and designing appropriate rehabilitation strategies (Fletcher and Schuchard, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with results of previous studies that reported delayed light adaptation and reduced contrast sensitivity in patients with AMD. 19,20 We did not find differences in drops of visual function between normal and AMD eyes in backlight-glare environments. The presence of a smaller pupil size in elderly population may account for the lack of effect of backlight glare, and therefore explain this finding.…”
Section: Discussionmentioning
confidence: 84%